Two-dimensional source potentials in a two-fluid medium for the modified Helmholtz's equation - B. N. Mandal; R. N. Chakrabarti (International Journal of Mathematics and Mathematical Sciences)
Velocity potentials describing the irrotational infinitesimal motion of two superposed inviscid and incompressible fluids under gravity with a horizontal plane of mean surface of separation, are derived due to a vertical line source present in either of the fluids, whose strength, besides being harmonic in time, varies sinusiodally along its length. The technique of deriving the potentials here is an extension of the technique used for the case of only time harmonic vertical line source. The present case is concerned with the two-dimensional modified Helmholtz's equation while the previous is concerned with the two-dimensional Laplace's equation.